Effects of Environmental Temperature on Capnodis tenebrionis Adult Phenology - Carmelo Peter Bonsignore (Psyche: A Journal of Entomology)
The phenology of Capnodis tenebrionis adults was presented with reference to two different climate conditions. In a temperate moderate-warm climate, adult density showed two separate peaks during the year: one in early summer of the overwintering generation and one with beetles emerging in the late summer. In a warmer semiarid climate, the overwintering adults and the new generation overlapped during summer with a continuous increase of adult density. The difference in the average annual temperature between areas during the study period was almost 3∘C, and, in the warmer area, the new generation of C. tenebrionis emerged at least one month earlier. To make a prediction of adult presence, a model utilizing degree-days was developed from data collected over a five-year period. Models obtained from equations (Logistic 4-parameter, y(x)=yo+a/(1+(x/xo)b)) of each year were developed to describe the relationship between degree-day accumulation (with a minimal threshold activity temperature of 14.21∘C calculated in the laboratory) and the cumulative percentage of adult presence. According to the overall model, the 50% of overwintering beetles occurred at 726 degree-days (Biofix: 1st March) and the emerging beetles occurred at 801 degree-days (Biofix: 1st July). The results show that a change in temperature is an important aspect that highlights the adaptability of this species.